Pengaruh Profitabilitas Terhadap Harga Saham Pada Perusahaan Food And Beverage Di BEI - Theo, Pascal; H, Andrey Adik; A, Luqman Harun (CV. ITTC INDONESIA, 2022)
This study aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) in Food and Beverages companies listed on the IDX in the 2019-2021 period. This research method uses quantitative methods. The samples used in the study were 9 Food and Beverages sub-sector companies listed on the Indonesia Stock Exchange. The analysis technique that been used in this research is multiple linear regression with using Eviews10 program. Based on the classical assumption test using normality test, multicollinearity test, autocorrelation test and heteroscedasticity test of the model are stated to have fulfilled assumption and no violation. Based on the results of feasibility test model using simultaneous determination coefficient test and simultaneous significance test showed that the regression model declared feasible to be used for research. The result of hypothesis testing shows that profitability has significant influence to the stock price.